Key factors influencing tree planting decision of farmers on farm land: A case study in Malakand, Pakistan - Khan, Pervez; Bui, Manh Hung; Le, Dinh Hai; Ahmad, Sohail; Khan, Faisal; Ullah, Sajjad; Ahmad, Adnan; Shiou Yih, Lee (Ecological Questions, 2024)
In order to cope with forest degradation and deforestation, farm forestry is a new tool for plantation purposes that combat these issues. Planting trees on farmlands is the most practical and viable approach given in the current situation in Pakistan for recovering the degraded forest lands, ensuring the sustainable use of marginal areas, and satisfying the rural requirements for the benefits of trees, both economically and non-economically. Therefore a socio-economic study of farmers in relation to tree planting is very important, to understand farmers perception about farm trees growing. In this study a total of 120 households were surveyed and interviewed in district Malakand for factor affecting farm tree planting decision. The result of step wise binary logistics regression analysis indicated that the factors including: Education level, Attitude of tree planting and silviculture knowledge were significantly influenced on tree planting decision of household in the study area. The total household income for planter was significantly higher than non-planter. The study result may provide the basis for proposing solution for future to strengthen trees planting decision for plantation, with the intention of promoting household engagement and attract farmers towards plantation activities in the study area.